2014
DOI: 10.1039/c4ta03010a
|View full text |Cite
|
Sign up to set email alerts
|

In situ solution plasma synthesis of nitrogen-doped carbon nanoparticles as metal-free electrocatalysts for the oxygen reduction reaction

Abstract: Nitrogen-doped carbon nanoparticles were successfully synthesized by a facile solution plasma process without the addition of metal catalysts. Organic liquid mixtures of benzene and pyrazine were used as the precursors for the synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 60 publications
2
76
1
Order By: Relevance
“…6B, the E onset of NS-MC1000 was located at 0.051 V, close to that of commercial Pt-C (0.086 V). This value is much higher than that of the lately reported nitrogen-doped carbon nanoparticles (À0.17 V) and nitrogen and sulfur co-doped mesoporous carbon vesicle (À0.16 V) [28,49] under the same experimental condition. Besides, it was clearly seen that the E onset , E 1/2 and j L of NS-MCs varied greatly with the annealing temperature.…”
Section: Resultscontrasting
confidence: 72%
“…6B, the E onset of NS-MC1000 was located at 0.051 V, close to that of commercial Pt-C (0.086 V). This value is much higher than that of the lately reported nitrogen-doped carbon nanoparticles (À0.17 V) and nitrogen and sulfur co-doped mesoporous carbon vesicle (À0.16 V) [28,49] under the same experimental condition. Besides, it was clearly seen that the E onset , E 1/2 and j L of NS-MCs varied greatly with the annealing temperature.…”
Section: Resultscontrasting
confidence: 72%
“…In general, selective synthesis of specific C-N bonding requires high temperature and pressure along with complicated instruments which makes the approach not economically favourable. [37][38] Recently, an emerging synthesis method, named solution plasma process (SPP), is specific for in situ heteroatom-doped carbon including synthesize N-doped [39][40][41][42] and/or B, P or Odoped carbon nanomaterials. [43][44] Previous findings from our group observed that crystallinity and graphitization of the synthesized carbon matrix increased significantly by introducing small amount of anthracene (C 14 H 10 ) as an additive in pure benzene.…”
Section: Introductionmentioning
confidence: 99%
“…In such systems, the plasma enables unique reactions such as C–H activation reactions at the interface between the solution and plasma, whereas conventional plasma induces random decomposition reactions. We have fabricated graphene, heterographene, nanocarbon sheets, and nanocarbon spheres via solution plasma from organic solutions containing solvents such as benzene, toluene, pyridine, or pyrazine60616263646566676869707172. Moreover, the reaction rate is substantially higher than the rates of other synthesis methods such as chemical vapor deposition and pyrolysis synthesis.…”
mentioning
confidence: 99%